Enhancing heteroazeotropic distillation thermodynamic flexibility boundaries by means of condenser overcooling. (January 2022) - Di Pretoro, Alessandro; Montastruc, Ludovic; Manenti, Flavio; Joulia, Xavier
Highlights: Process feasibility studies should consider a wide range of operating conditions if disturbances are likely to occur. Combining residue curves and LLE diagrams allows a better understanding of the heteroazeotropic distillation unit. The top vapor overcooling in the condenser and downstream decantation enhance the separation thermodynamic flexibility. Abstract: When chemical processes involve the treatment of raw materials characterized by unstable properties over the year' s seasons, upstream perturbations could affect the downstream operation feasibility. This research work discusses how non-idealities can be exploited to enhance the flexibility of the operation for an ABE/W purification section. In particular, the effects of condenser overcooling on the allowed feed composition perturbations are analyzed in case of distillation process. For this purpose, an innovative methodology based on residue curve maps coupled with liquid-liquid equilibrium is presented. Calculations have been performed by means of an interface between the Simulis Thermodynamics®software for components characterization and Matlab. A graphical tool for mixtures up to four components is provided as well. This procedure extends the available methodology for the conventional distillation feasibility study by including specifications in terms of recovery ratio and by its generalization to distillation trains and Dividing Wall Columns as well.